2012
DOI: 10.1007/s00268-012-1496-1
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age Affects Liver Regeneration during Early Period in the Graft Liver and Late Period in the Remnant Liver after Living Donor Liver Transplantation

Abstract: Background The aim of the present study was to evaluate the influence of donor age on liver regeneration and surgical outcomes in recipients and donors. Patients and methods Among 101 cases of adult‐to‐adult living donor liver transplantation (LDLT) between March 2002 and March 2011, according to donor age: younger (Y) <50 years of age or older (O) ≥50 years of age, the donors and recipients using right (R) or left (L) graft were divided into groups Y/R (n = 51) and O/R (n = 17), and groups Y/L (n = 26) and O/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 54 publications
1
59
3
Order By: Relevance
“…In most other studies, incomplete liver regeneration was reported even up to 4 years after donation (33). Regarding factors influencing regeneration, some studies have suggested that age had an impact on regeneration (25,30,41), while several other studies showed that there was no impact of donor age on liver regeneration (16,27,33,38,45). We did find that increasing donor age had a negative influence on early as well as late volumetric recovery (on POD7 and POD365).…”
Section: Discussionmentioning
confidence: 37%
“…In most other studies, incomplete liver regeneration was reported even up to 4 years after donation (33). Regarding factors influencing regeneration, some studies have suggested that age had an impact on regeneration (25,30,41), while several other studies showed that there was no impact of donor age on liver regeneration (16,27,33,38,45). We did find that increasing donor age had a negative influence on early as well as late volumetric recovery (on POD7 and POD365).…”
Section: Discussionmentioning
confidence: 37%
“…For example, our study concurs with others in showing a worse outcome with the use of older donors [5,21,22] (Tables 8 and 9). While the mechanism for the detrimental effect of older donor age on renal recovery is not fully understood, a slower onset of hepatic allograft function may be contributory [23,24]. There is also evidence that the livers from older donors are at greater risk for ischemia-reperfusion injury [25-27], although there is no universal agreement on this point [28].…”
Section: Discussionmentioning
confidence: 99%
“…Methods of treatment include liver transplantation and liver resection, with liver regeneration making extensive liver resection or living donor liver transplantation possible. Several donor‐associated factors may affect liver regeneration after transplantation, including donor age, ischemic injury, and graft size . The loss of regenerative capacity is the most dramatic age‐associated alteration of preserved livers .…”
Section: Introductionmentioning
confidence: 99%